STRENGTHENING THE ROLE OF PARENTS AS THE MAIN FOUNDATION FOR THE FORMATION OF MORALITY CHILDREN IN PLAKPAK VILLAGE - Putri, Sari Nusantara; Muhyatun, Muhyatun; Alfiansyah, Alfiansyah; Ramin, Moh. (LP2M IAI Al-Khairat Pamekasan, 2025)
This community service activity aims to raise parental awareness of their role as the first agents of moral education in children. Conducted through an educational seminar in Plakpak Village, Pegantenan District, Pamekasan Regency, the program implemented a Participatory Action Research (PAR) model to explore and address issues surrounding moral decline among students. The seminar provided insights on parenting approaches, character education, and moral development in children. Results showed a strong interest from parents in understanding moral education and the importance of collaboration between families and educational institutions. Despite limited attendance, the activity succeeded in promoting constructive dialogue and awareness on parenting practices that support character development.